Strategic HSM in Educational Institutions: A Conceptual Framework for Improving Educational Quality: Manajemen Keamanan dan Keselamatan Kerja (HSM) Strategis di Lembaga Pendidikan: Kerangka Konseptual untuk Meningkatkan Kualitas Pendidikan - Luqman Erfan; Agus Fawait; Wafi Al Hajjaj (Mapendis: Jurnal Manajemen Pendidikan Islam, 2024)
Educational institutions increasingly face complex challenges related to quality assurance, accountability, and sustainability in a rapidly changing educational environment. In this context, the strategic management of human resources has become a critical determinant of institutional effectiveness and educational quality. This article aims to develop a conceptual framework for Strategic Human Resource Management (SHRM) in educational institutions as a means of enhancing educational quality. Employing a qualitative conceptual research design, the study is based on a systematic review and analytical synthesis of key theories and scholarly literature in the fields of human resource management, educational management, and organizational studies. The findings reveal that SHRM in educational institutions operates through several interrelated dimensions, including strategic alignment, human capital development, performance management, organizational culture, leadership integration, adaptability to environmental change, and institutional sustainability. These dimensions function as a coherent system that links human resource practices with long-term educational objectives rather than short-term administrative needs. The discussion highlights that educational quality improvement is most sustainable when human resource management is embedded within the strategic core of the institution and aligned with its vision and mission. This study contributes theoretically by integrating fragmented literature into a unified conceptual framework and provides practical insights for educational leaders seeking to position human resources as strategic drivers of quality improvement. The framework also offers a foundation for future empirical research on SHRM in diverse educational contexts.